Evolutionary process toward avian-like cephalic thermoregulation system in Theropoda elucidated based on nasal structures. Issue 4 (12th April 2023) - Tada, Seishiro; Tsuihiji, Takanobu; Matsumoto, Ryoko; Hanai, Tomoya; Iwami, Yasuko; Tomita, Naoki; Sato, Hideaki; Tsogtbaatar, Khishigjav
Abstract : It has long been discussed whether non-avian dinosaurs were physiologically closer to ectotherms or endotherms, with the internal nasal structure called the respiratory turbinate present in extant endotherms having been regarded as an important clue for this conundrum. However, the physiological function and relevance of this structure for dinosaur physiology are still controversial. Here, we found that the size of the nasal cavity relative to the head size of extant endotherms is larger than those of extant ectotherms, with that of the dromaeosaurid Velociraptor being below the extant endotherms level. The result suggests that a large nasal cavity accommodating a well-developed respiratory turbinate is primarily important as a thermoregulation apparatus for large brains characteristic of endothermic birds and mammals, and the nasal cavity of Velociraptor was apparently not large enough to carry out this role required for an endothermic-sized brain. In addition, a hypothesis that the enlargement of the nasal cavity for brain cooling has been associated with the skull modification in the theropod lineage toward modern birds is proposed herein. In particular, the reduction of the maxilla in derived avialans may have coincided with acquisition of the avian-like cephalic thermoregulation system.